Towards an integrated framework for the configuration of modular micro assembly systems - Smale, Daniel M. (2011)
The future of manufacturing in high-cost economies is to maximise responsiveness to change whilst simultaneously minimising the financial implications. The concept of Reconfigurable Assembly Systems (RAS) has been proposed as a potential route to achieving this ideal. RASs offer the potential to rapidly change the configuration of a system in response to predicted or unforeseen events through standardised mechanical, electrical and software interfaces within a modular environment. This greatly reduces the design and integration effort for a single configuration, which, in combination with the concept of equipment leasing, enables the potential for reduction in system cost, reconfiguration cost, lead time and down time.